Hysterosalpingogram in evaluation of primary and secondary infertility: a two year study at a tertiary care hospital of South India - Reddy, Gurram Swetha; Jyothi, Gandavaram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Infertility globally is a raising threat and problem associated with significant social and psychological problem. Infertility currently affects about 10 to 14 percent of the Indian population, with higher rates in urban areas where one out of six couples is impacted. Patency of the tubes, structure of uterus and cervix can be visualized by hysterosalpingogram which is a simple safer inexpensive investigation of choice in cases of infertility. Objective of this study was to study the role of hysterosalpingography (HSG) in cases of primary and secondary infertility and to observe the structural abnormalities of cervix, uterus and fallopian tubes. Methods: A two year prospective study was conducted on cases of primary and secondary infertility attending the OPD of infertility clinic. HSG was performed on the subjects included in study and findings were noted. Analysis was done by Microsoft excel spread sheet. Results: A total of 286 cases with 11.19% of primary infertility and 88.81% of secondary infertility evaluated by HSG. Mean age of the study group was 35.16±2.8 years. 74.83% had abnormal findings, with 20.28% having normal uterine cavity with uterine filling defect being the common abnormality. Two congenital anomalies of uterus were noted. Tubal occlusion was seen in 8.39% right and 9.09% left cases. Hydrosalpinx was observed in 7.69% of right and 9.79% of left cases. Conclusions: To conclude, women presenting with infertility should be evaluated for tubal pathology. The tubal pathologies like occlusion or hydrosalpinx may be due to infections or post surgical sequelae. HSG remains one of the diagnostic backbone in infertility even availability of new modalities.